Church and poverty in South Africa: Historical analysis and missional ecclesiology - Christoffel B. Prinsloo; Willem A. Dreyer (HTS Teologiese Studies/Theological Studies)
Poverty remains a critical socio-economic challenge in South Africa, deeply rooted in the country’s history of colonialism and apartheid. This article examines the multifaceted role of churches in poverty alleviation efforts in South Africa, spanning both historical and contemporary contexts. Through analysis of historical records and contemporary literature, it argues that while churches have significantly addressed poverty, a more comprehensive and transformative approach is needed. The study proposes adopting a missional ecclesiology framework to enhance the effectiveness of church-led poverty alleviation initiatives, offering insights into how churches can engage more deeply and sustainably in the fight against poverty.